KEADILAN BAGI INVESTOR DALAM KEGIATAN INVESTASI ILLEGAL (BINARY OPTION) TERHADAP HUKUM INVESTASI DI INDONESIA - Bayu Abdillah; Belva Vidaloka Chrisari; Bhim Prakoso (Bajang Institute, 2023)
This article discusses the issue of justice for investors who have fallen victim to illegal investment practices, specifically binary options, in Indonesia. The author utilizes normative research methods, using both a statutory approach and a conceptual approach, to explore how the investors can obtain compensation and achieve justice. Compensation for victims is established as the responsibility of the offenders, as specified in Article 7 of Law No. 31 of 2014 concerning Witness and Victim Protection. Additionally, consumer protection laws, such as Article 9 paragraph (1) letter k of Law No. 8 of 1999 on Consumer Protection, and Bappebti Regulation No. 3 of 2019 on Commodities, provide further safeguards for investors. By understanding and applying these legal provisions, it is hoped that victims can recover their losses and receive fair compensation.